2009
DOI: 10.1182/blood.v114.22.3056.3056
|View full text |Cite
|
Sign up to set email alerts
|

Human ALDH-Bright Bone Marrow Cells Produce Paracrine Factors That Protect Endothelial Cells From Hypoxic and Nutritional Stress.

Abstract: 3056 Poster Board II-1032 Human bone marrow cell populations isolated by sorting cells on the basis of high aldehyde dehydrogenase expression (ALDHbr cells) include endothelial, mesenchymal, and other progenitor cells (Gentry et al, 2007, Cytotherapy 9, 259). These cell populations home to and are retained at ischemic endothelium, induce angiogenesis, and effect restoration of tissue perfusion in a mouse hind limb ischemia model (Cappoccia et al, 2009 Blood 113, 5340.) Critical li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Other studies have validated that these cells act through paracrine mechanisms. Smith et al reported that human BM-derived ALDH hi cells expressed angiogenic cytokines that protect endothelial cells from ischemic damage (112), and another study demonstrated that coculture of ALDH hi cells promoted the survival of HUVECs under growth serum-free conditions as opposed to coculture with ALDH lo cells, which resulted in death of HUVECs. In a hindlimb ischemia mouse model, transplantation of ALDH hi cells enhanced recovery of perfusion and capillary density.…”
Section: Aldehyde Dehydrogenase Activitymentioning
confidence: 99%
“…Other studies have validated that these cells act through paracrine mechanisms. Smith et al reported that human BM-derived ALDH hi cells expressed angiogenic cytokines that protect endothelial cells from ischemic damage (112), and another study demonstrated that coculture of ALDH hi cells promoted the survival of HUVECs under growth serum-free conditions as opposed to coculture with ALDH lo cells, which resulted in death of HUVECs. In a hindlimb ischemia mouse model, transplantation of ALDH hi cells enhanced recovery of perfusion and capillary density.…”
Section: Aldehyde Dehydrogenase Activitymentioning
confidence: 99%